2015
DOI: 10.2337/dc14-2469
|View full text |Cite
|
Sign up to set email alerts
|

Seeing Is Believing: Using Skype to Improve Diabetes Outcomes in Youth

Abstract: OBJECTIVEThe objective of this study was to compare the relative effectiveness of two modes of delivering Behavioral Family Systems Therapy for Diabetes (BFST-D) to improve adherence and glycemic control among adolescents with type 1 diabetes with suboptimal glycemic control (HbA 1c ‡9.0% [ ‡74.9 mmol/mol]): face to face in clinic (Clinic) and Internet videoconferencing (Skype) conditions. RESEARCH DESIGN AND METHODSAdolescents aged 12 to 18 years and at least one adult caregiver were randomized to receive BFS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
108
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(110 citation statements)
references
References 33 publications
1
108
0
1
Order By: Relevance
“…114 Adherence to treatment and glycaemic control were also similar. 91 However, losses to follow-up were high: of the 47 (out of 92) participants randomised to Skype sessions, follow-up data were available for only 32.…”
Section: Research Context and Relevant Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…114 Adherence to treatment and glycaemic control were also similar. 91 However, losses to follow-up were high: of the 47 (out of 92) participants randomised to Skype sessions, follow-up data were available for only 32.…”
Section: Research Context and Relevant Literaturementioning
confidence: 99%
“…[88][89][90][91][92][93][94][95][96][97][98] A number of published studies focus broadly on video or remote consulting (e.g. exploring issues of usability and acceptability).…”
Section: Evidence Relating To the Use Of Virtual Consultationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specialized healthcare professionals provide specific education, counseling, and monitoring concerning difficult parenting tasks or problems. Harris, Freeman, and Duke (2015), for example, used a structured parent and adolescent training program through scheduled Skype calls with a psychologist to improve diabetes outcome in youth.…”
Section: Videoconferencing With Therapist or A Specialized Healthcarementioning
confidence: 99%
“…Across these studies, despite reported benefits (e.g. in terms of increased access for patients [9,[28][29][30] particularly those with complex needs, [31] patient and clinician satisfaction with the remote option, [23,[32][33][34][35] potential time/cost savings, [8,36,37] improvement in self-management skills, [38] and improved compliance to treatment and/or clinical outcomes [17,22,24,31,[39][40][41][42][43]) small sample sizes (e.g. five patients) and high losses to follow-up prevent any unqualified conclusion that remote consultations are 'effective'.…”
Section: Introduction Backgroundmentioning
confidence: 99%